MENINGKATKAN KOMPETENSI SUMBER DAYA MANUSIA DALAM MENGHADAPI DUNIA KERJA MELALUI PELATIHAN PEMERIKSAAN KUALITAS PRODUK MANUFAKTUR - Supriyati Supriyati; Hasyrani Windyatri; Hana Silvia Dwi Putri; Siti Rahayu; Retno Fitri Astuti (Universitas Mataram, 2025)
Vocational High Schools (SMK) have an important role in preparing graduates who are ready to work and able to meet industry needs. However, there is still a competency gap between students' abilities and the demands of the world of work, especially in terms of product quality inspection. This Community Service Activity (PKM) aims to improve SMK students' understanding and skills regarding product quality concepts, quality standards, and manufacturing product inspection techniques through training and practice-based learning. Activities were carried out at one of the SMKs in the Cikarang area and were attended by 20 students. Training included lectures on basic product quality concepts, demonstrations on the use of measuring tools such as rulers and calipers, product inspection practices, as well as discussions and evaluations of inspection results. Results showed a significant improvement in students' understanding of quality concepts and product inspection procedures, with an average post-test score increase of 58%. A total of 85% of participants were able to perform simple product inspections in accordance with standard operating procedures (SOP). In addition, this training also contributed to the strengthening of soft skills such as accuracy, discipline, responsibility, cooperation, and critical thinking skills. This program of community service has proven effective in reducing the skill gap between education and industry needs, as well as improving the readiness of vocational school students to face the challenges of modern manufacturing.